Keeping the body in play: Pain, injury, and socialization in male rugby - Fenton, L.; Pitter, R. (Research Quarterly for Exercise and Sport, 2010)
This paper discusses participant observation studies of two rugby seasons - one rural high school and one university club - in which one author served as a first aid provider and student athletic trainer, respectively. Through analysis using triangulation, we explored how the rules, athlete's status, and return-to-play boundary influenced decisions when the athlete was in pain and/or injured. The results varied between the groups, suggesting a need for further research on behavioral patterns of high school and university athletes. This study effectively illustrates how social pressure and an athlete's socialization affect individual responses to pain and/or injury and how both pressure an athlete to learn to physically tolerate increasing amounts of pain.